2019
DOI: 10.3389/fimmu.2019.00499
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Vaccine Encoding the VAA Gene of Vibrio anguillarum Induces a Protective Immune Response in Flounder

Abstract: Vibrio anguillarum is a pathogenic bacterium that infects flounder resulting in significant losses in the aquaculture industry. The VAA protein previously identified in flounder is associated with a role in immune protection within these fish. In the present study, a recombinant DNA plasmid encoding the VAA gene of V. anguillarum was constructed and its potential as a DNA vaccine, to prevent the infection of V. anguillarum in flounder fish, investigated. We verified the expression of the VAA protein both in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 70 publications
(89 reference statements)
3
12
0
Order By: Relevance
“…The results of PCR and RT-PCR demonstrated that the Hrp1 and IL-34 genes were only found in the muscle tissue of fish immunized with pcHrp1, pcIL-34 or pcHrp1+pcIL-34, indicating that the recombinant DNA plasmids could avoid local degradation and uptake by the muscle cells at the injection site, resulting in expression at transcription levels. Our results are in agreement with studies investigated in other fish species, including channel catfish [23], orange-spotted grouper [47], snakehead fish [16,66], and the Japanese flounder [11,67]. It is reported that cell membrane permeability and susceptibility of foreign DNA to host enzymes is one of the pivotal factors to evaluate the efficiency of the cellular uptake of DNA vaccines [68]; hence, further studies are required to estimate the efficiency of the cellular uptake of pcIL-34, pcHrp1 and pcHrp1+pcIL-34.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of PCR and RT-PCR demonstrated that the Hrp1 and IL-34 genes were only found in the muscle tissue of fish immunized with pcHrp1, pcIL-34 or pcHrp1+pcIL-34, indicating that the recombinant DNA plasmids could avoid local degradation and uptake by the muscle cells at the injection site, resulting in expression at transcription levels. Our results are in agreement with studies investigated in other fish species, including channel catfish [23], orange-spotted grouper [47], snakehead fish [16,66], and the Japanese flounder [11,67]. It is reported that cell membrane permeability and susceptibility of foreign DNA to host enzymes is one of the pivotal factors to evaluate the efficiency of the cellular uptake of DNA vaccines [68]; hence, further studies are required to estimate the efficiency of the cellular uptake of pcIL-34, pcHrp1 and pcHrp1+pcIL-34.…”
Section: Discussionsupporting
confidence: 93%
“…However, various factors, such as vaccine type, antigen dose, vaccination schedule (with or without booster), vaccine delivery route and the application of adjuvants can influence the vaccine efficacy [95]. Similarly, recent vaccine studies in Vibrio alginolyticus [47,96], Vibrio anguillarum [10,11,97,98], Vibrio harveyi [48], and Edwardsiella tarda [13] indicated that vaccination of recombinant proteins in combination with adjuvants could confer higher RPS levels than immunization with a DNA vaccine alone. Interestingly, pcHrp1, when co-administrated with pcIL-34, could enhance the protection by generating better RPS (82.14%) compared with rHRP1 emulsified with ISA 763 A VG; hence, this result might explain the superiority of IL-34 as an molecular adjuvant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, based on the bioinformatics analysis of amino acid sequences, two 14-aa epitope peptide candidates were identified and employed as immunogens to develop mAbs against flounder CD4-1 and CD4-2. Although polyclonal antibodies against recombinant CD4-1 and CD4-2 proteins of flounder were produced, respectively, the dynamic change in the percentages of CD4 + cells was used as an indicator of the fish health status and vaccine evaluation in our lab [19][20][21][22][23][24][25] . However, some characteristics of polyclonal antibodies make them incomparable to monoclonal antibodies, and mAbs against CD4 molecules are sustainable and powerful tools in the functional study of fish CD4 + T cells.…”
Section: Expression Of Transcription Factors and Cytokines In Cd4mentioning
confidence: 99%
“…Three CD4 + T cell subsets, CD4-1 single-positive T cells, CD4-2 single-positive T cells and CD4-1/CD4-2 doublepositive T cells, were found in different proportions in flounder peripheral blood, spleen and head kidney, and CD4-1 + /CD4-2 + T cells were the majority of CD4 + T cells 18 . In addition, dynamic changes in the percentages of CD4 + cells were detected as indicators of fish health and vaccine evaluation [19][20][21][22][23][24][25] . In this paper, to further explore the function of CD4 + Th cells, monoclonal antibodies against the flounder CD4-1 and CD4-2 molecules were developed.…”
mentioning
confidence: 99%